Optimization of amorphous silicon solar cells through photonic crystals for enhanced optical properties - Hassan Sayed; Ashour M. Ahmed; Ali Hajjiah; M. A. Abdelkawy; Arafa H. Aly (Scientific Reports)
Abstract Amorphous silicon solar cells have emerged as a promising technology for harnessing solar energy due to their cost-effectiveness and flexibility. However, their efficiency is constrained by low sunlight absorption resulting from the material’s indirect band gap and intrinsic properties of amorphous silicon. This study employs theoretical modeling to investigate the impact of incorporating one-dimensional ternary photonic crystals (1D-Ternary-PCs) as anti-reflection coatings (ARCs) and one-dimensional binary PCs as back reflectors to enhance the optical properties of amorphous silicon (a-Si) solar cells. The investigation utilizes the COMSOL Multiphysics program, based on the finite element method (FEM), to simulate and analyze the optical characteristics of PC-enhanced a-Si solar cells. The modeling involves designing and optimizing ternary PC structures, followed by numerical simulations to assess their anti-reflection performance. Additionally, designing one-dimensional binary PCs optimized to create a photonic band gap within the transmitted spectrum to act as a back reflector. The study systematically examines the impact of various parameters such as layer thickness, refractive indices, and incident angles on the optical properties of PC-enhanced a-Si solar cells, offering insights into the potential of one-dimensional PCs as effective back reflectors and ARCs for enhancing light absorbance and overall efficiency.